Fostamatinib, a Spleen Tyrosine Kinase Inhibitor, Exerts Anti-Inflammatory Activity via Inhibiting STAT1/3 Signaling Pathways - Guo R; Liao H; Meng Y; Shi X; He Y; Zhu Z; Guo W (Journal of Inflammation Research)
Ran Guo,1 Hanjing Liao,2 Yinuo Meng,3 Xiaoyi Shi,4 Yuting He,4 Zhixiang Zhu,2 Wenzhi Guo1,4 1Henan Key Laboratory of Digestive Organ Transplantation, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450052, People’s Republic of China; 2Modern Research Center of Traditional Chinese Medicine, Beijing Research Institute of Chinese Medicine, Beijing University of Chinese Medicine, Beijing, 100029, People’s Republic of China; 3Department of Faculty of Life Sciences & Medicine, King’s College London, London, UK; 4Department of Hepatobiliary and Pancreatic Surgery, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450052, People’s Republic of ChinaCorrespondence: Wenzhi Guo, Henan Key Laboratory of Digestive Organ Transplantation, the First Affiliated Hospital of Zhengzhou University, No. 1 Jianshe East Road, Erqi District, Zhengzhou, 450052, People’s Republic of China, Email fccguowz@zzu.edu.cn Zhixiang Zhu, Modern Research Center for Traditional Chinese Medicine, Beijing Research Institute of Chinese Medicine, Beijing University of Chinese Medicine, No. 11 Beisanhuan East Road, Chaoyang District, Beijing, 100029, People’s Republic of China, Email zzx@bucm.edu.cnBackground: Fostamatinib is the first spleen tyrosine kinase inhibitor approved for the treatment of chronic adult immune thrombocytopenia via blocking autoantibody-mediated platelet phagocytosis. Nevertheless, the potential of fostamatinib as therapeutic agent against acute inflammatory diseases has not been examined. This study aimed to investigate the effects of fostamatinib on the activation of macrophages and neutrophils and its therapeutic effects on SIRS.Methods: First, RT-qPCR and ELISA were used to detect the effects of fostamatinib on the expression and secretion of inflammatory factors by peritoneal macrophages (PMs) induced with TLR agonists. The activation and ROS release of neutrophils were detected by flow cytometry. Subsequently, the therapeutic effect of fostamatinib on LPS-induced SIRS in mice was examined. Finally, we also explored the underlying mechanisms of fostamatinib exerting pharmacodynamic effects by analyzing its effects on LPS-induced gene expression profile and the activation of signaling pathways in PMs through transcriptome sequencing and Western blot.Results: We found that fostamatinib inhibited the expression and secretion of TNF-α, IL-6, CCL2, CCL3, and CXCL10 (*P < 0.05) in PMs induced by LPS. Fostamatinib also reduced the activation of neutrophils stimulated by LPS, and suppressed the release of ROS by neutrophils. In SIRS mice, fostamatinib diminished the levels of inflammatory factors, and inhibited the excessive consumption of neutrophils in bone marrow. Transcriptome sequencing results showed that fostamatinib significantly inhibited the transcription of Cxcl10, Isg20, Mx1, Rsd2, etc. (*P < 0.05) in PMs induced by LPS. Meanwhile, fostamatinib selectively blocked the phosphorylation of STAT1 and STAT3 in PMs induced by LPS and cytokines (IFN-γ and IL-6).Conclusion: Fostamatinib can significantly inhibit LPS-induced inflammatory response through blocking STAT1/3 signaling pathways and has the potential to be used in the therapy of acute inflammatory diseases, especially SIRS and sepsis, which are resulting from the infection of Gram-negative bacteria.Keywords: fostamatinib, inflammation, macrophages, neutrophils, STAT1/3 signaling pathways, systemic inflammatory response syndrome